Review paper Catechol-O-methyltransferase: potential relationship to idiopathic hypertension - Mantione, Kirk J.; Kream, Richard M.; Stefano, George B. (Archives of Medical Science, 2010)
Catecholamine signaling pathways in the peripheral and central nervous systems (PNS, CNS, respectively) utilize catechol-O-methyltransferase (COMT) as a major regulatory enzyme responsible for deactivation of dopamine (DA), norepinephrine (NE) and epinephrine (E). Accordingly, homeostasis of COMT gene expression is hypothesized to be functionally linked to regulation of autonomic control of normotensive vascular events. Recently, we demonstrated that morphine administration in vitro resulted in decreased cellular concentrations of COMT-encoding mRNA levels, as compared to control values. In contrast, cells treated with E up regulated their COMT gene expression. In sum, these observations indicate a potential reciprocal linkage between end product inhibition of COMT gene expression by E and morphine. Interestingly, the observed effects of administered E on COMT gene expression suggest an enhancement of its own catabolism or, reciprocally, a stimulation morphine biosynthesis.